2017
DOI: 10.1002/adfm.201605989
|View full text |Cite
|
Sign up to set email alerts
|

Fluoroethylene Carbonate Additives to Render Uniform Li Deposits in Lithium Metal Batteries

Abstract: Lithium (Li) metal has been considered as an important substitute for the graphite anode to further boost the energy density of Li‐ion batteries. However, Li dendrite growth during Li plating/stripping causes safety concern and poor lifespan of Li metal batteries (LMB). Herein, fluoroethylene carbonate (FEC) additives are used to form a LiF‐rich solid electrolyte interphase (SEI). The FEC‐induced SEI layer is compact and stable, and thus beneficial to obtain a uniform morphology of Li deposits. This uniform an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
962
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 1,328 publications
(989 citation statements)
references
References 81 publications
23
962
4
Order By: Relevance
“…The Li 1s spectra (Figure 3h,k) exhibit three characteristic peaks at 56.2, 55.3, and 54.5 eV ascribed to LiF, Li 2 CO 3 , and ROCO 2 Li, due to the reaction of carbonate electrolyte with Li metal. It is reported that LiF could contribute to the formation of a stable and uniform SEI layer and suppressing the Li dendrite growth, [16,37,38] resulting in stable Li plating/stripping cycling. [35,36] It can be seen that the relative amount of LiF is increased by the use of the hybrid electrolyte compared with the separator.…”
Section: Doi: 101002/advs201802353mentioning
confidence: 99%
“…The Li 1s spectra (Figure 3h,k) exhibit three characteristic peaks at 56.2, 55.3, and 54.5 eV ascribed to LiF, Li 2 CO 3 , and ROCO 2 Li, due to the reaction of carbonate electrolyte with Li metal. It is reported that LiF could contribute to the formation of a stable and uniform SEI layer and suppressing the Li dendrite growth, [16,37,38] resulting in stable Li plating/stripping cycling. [35,36] It can be seen that the relative amount of LiF is increased by the use of the hybrid electrolyte compared with the separator.…”
Section: Doi: 101002/advs201802353mentioning
confidence: 99%
“…19 Another critical problem with Li-ions is that they may suffer the effect of plating instead of alloying with the Si, triggering the formation of dendrites, which might produce internal short circuits in the battery. 20 Over the years several investigations have been done on how to prevent the growth of dendrites in a battery, [21][22][23][24] but only a few theoretical studies of this phenomenon have been reported 25,26 and despite them, the exact mechanisms of growing dendrite are still elusive. 9,27 As mentioned before, Si anodes swell about 300% and hard SEI such as LiF most likely crack due to such expansion, allowing Li-ions to be reduced and then nucleate into the cracks forming dendrites.…”
Section: Introductionmentioning
confidence: 99%
“…These C-containing species could be derived from the reductions of TFSI − anions, DME, and FEC, [29,30] resulting in the formation of organic components as observed in TEM ( Figure S4a, Supporting Information). The interpeak distance shows a typical ∆metal = 6.0 eV, proving the presence of metallic Ag.…”
Section: Li-ag-lif Surface For LI Metal Protectionmentioning
confidence: 99%